Control of cylinder wake using oscillatory morphing surface - Zeng, Lingwei (2024)
In this study, the wake of a cylinder was actively controlled by the cylinder's oscillatory morphing surface. Experiments were conducted in a closed-loop water channel. A cylinder of diameter 36 mm was placed in 0.09 m/s water flow, resulting in the Reynolds number 3240 and the vortex shedding frequency around 0.5 Hz. The cylinder's morphing surface oscillated at four different frequencies, i.e., 0.5, 1, 2, and 4 Hz. It was found that, compared to the rigid circular cylinder, the cylinder with oscillatory morphing surface can generally produce a smaller vortex formation length, especially at intermediate oscillation frequencies. The shear layers developed from the cylinder transit and roll up earlier due to enhanced flow instabilities. With the highest-frequency oscillations, the shear layer develops into a train of many small vortices that follow the trace of undisturbed shear layer. This study reveals some physical insights into this novel flow control method, which could be useful in future engineering applications.